An Analysis of Radiation Worker Safety at SAMOP Facility PSTA-BATAN Yogyakarta Using MCNP6 - Suharyana Suharyana Suharyana (BATAN, 2020)
It has been done the calculation of g dose simulation received radiation worker around SAMOP using MCNP6. The fuel SAMOP was modelled on the solution of uranyl nitrate (UO2(NO3)2) with enrichment of 19.75% and a concentration of 300 g U/L. SAMOP was operated on a power of 600 watts and burn up for 6 days using ORIGEN2. From the simulation burn up acquired information g radiation contribution used to calculate the dose received by radiation workers. The Calculation of the dose rate using MCNP6 at a distance of 225 cm from SAMOP without shielding obtained the result of g dose the amount of (11,217.39 ± 0.35) mSv/hour with the estimated working time of radiation workers at 0.02 hours/week. Addition of the barite concrete shielding with a thickness of 47.69 cm at a distance of 225 cm from SAMOP using an extrapolation approach based on the variation of the shielding thickness of simulation calculation results obtained g dose rate of 5.21 mSv/hour and estimated time maximum work of 36.98 hours/week.